Chapter 2 Defining the Term Samhandling - Torgersen, Glenn-Egil (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"In this chapter we will demonstrate that samhandling has a different qualitative meaning from other similar concepts. The term "samhandling" is used by many organizations, researchers and textbook authors without clarifying the rationale for its use (Torgersen & Steiro, 2009). The word samhandling is built on a distinct cultural foundation. Therefore, we think it is necessary to describe Norwegian culture briefly, to enable the reader to understand the basis of samhandling. The chapter presents a definition of samhandling that was originally presented by Torgersen & Steiro (2009). Samhandling is distinguished from cooperation/teamwork by three core attributes which we can call the identity of samhandling: focus on complementarity, exchange and utilization of the participants' various skills, experiences, backgrounds and cultures, and coordination of these factors in efforts towards a common goal in a work situation or meeting. Samhandling has a higher relative ambition level than the corresponding processes covered by the expressions "collaboration", "cooperation" and "coordination". Increased complexity and relations between stakeholders call for a focus on complementary handling in action, that is, samhandling. The following competencies were identified in order for good samhandling to occur: trust, assurance, well-being, belonging, clarity, time and tolerance."